A zwitterionic near-infrared dye linked TrkC targeting agent for imaging metastatic breast cancer. Issue 10 (24th September 2018) - Yang, Zhen; Usama, Syed Muhammad; Li, Feng; Burgess, Kevin; Li, Zheng
Abstract : A probe that conjugated a TrkC targeting agent with a zwitterionic near-infrared dye was reported for imaging of metastatic breast cancer. Abstract : Much effort has been devoted to targeting agents for imaging and chemotherapy of tumors in cancer research, but there remain significant unmet needs in that area. We have reported a series of preclinical TrkC targeting agents for diagnoses and treatment of metastatic breast cancer; however, with respect to optical imaging, there are limitations to the agents already disclosed. In this work, a TrkC targeting fragment was equipped with a zwitterionic cyanine dye to give a near-infrared probe for in vivo imaging of metastatic breast tumors, with excitation and emission wavelengths of 760 and 780 nm, respectively, and facilitate the aqueous dissolution of the final design. To our delight, the newly developed probe maintained the specific targeting to TrkC + 4T1 metastatic breast tumor cells as well as the TrkC + metastatic breast tumor tissue. Upon injection into 4T1-tumor-bearing mice, the tumor was visualized in vivo and ex vivo through the fluorescence signal of the probe. These data seem to encourage further investigations toward developing a TrkC targeting agent for the diagnosis of metastatic breast tumors.